Newborn Adipokines and Birth Outcomes. Issue 4 (July 2015) - Yeung, Edwina H.; McLain, Alexander C.; Anderson, Nancy; Lawrence, David; Boghossian, Nansi S.; Druschel, Charlotte; Bell, Erin
Abstract Background Adipokines can serve as a measure of adipose tissue activity. Although birthweight correlates with neonatal adiposity, findings for cord blood levels of adipokines and birth outcomes have been conflicted. Therefore, we determined the cross‐sectional associations between adipokines measured in newborn dried blood spots (DBS) and birth outcomes. Methods The Upstate KIDS study enrolled mothers and infants from 2008 to 2010. Among infants whose parents consented to the use of residual DBS from newborn screening, 2397 singletons and 1240 twins had adipokine measurements from the Human Obesity Panel (R&D Systems) by Luminex. Odds ratios were estimated by multivariable logistic regression for risk of birth outcomes of preterm delivery (<37 weeks for singletons, <32 for twins) and small‐for‐gestational age (SGA <10th for singletons and <3rd for twins age‐ and sex‐specific percentiles) by adipokine quintiles. Generalised estimating equations were applied to account for correlations between twins. Results Singletons in the lowest compared with the highest quintile of adiponectin were more likely preterm (adjusted odds ratio 3.26; 95% confidence interval [CI] 1.99, 5.34) and SGA (1.81; [95% CI 1.18, 2.77]). Similar associations were observed among twins. Resistin was associated with preterm birth (Q1 vs. Q5: 2.08; [95% CI 1.20, 3.62]) only among singletons. Adipsin had inconsistent associations after adjustment. Conclusions This large population‐based study demonstrates that newborn DBS‐measured adipokines are associated with birth outcomes, particularly preterm birth and SGA among those with lower adiponectin levels regardless of plurality.